Pharmacokinetics, Tissue Distribution, and Excretion Study of Cajanonic Acid A in Rats by UPLC-MS/MS - Zhang, Li; Chen, Rui; Ban, Yujuan; Cai, Jin; Peng, Jingang; Huang, Jing; Wang, Jianta; Chen, Wenzhang; Gao, Xiuli; Zhou, Xunrong; Tang, Lei (Planta Medica, 2020)
Cajanonic acid A (CAA), a prenylated stilbene derivative extracted from the leaves of pigeon pea (Cajanus cajan), has been reported to possess inhibitory activity on the peroxisome proliferator-activated receptor gamma (PPARγ) and protein tyrosine phosphatase 1B (PTP1B). Its hypoglycemic activity in rats is comparable to that of the approved antidiabetic agent rosiglitazone. Therefore, CAA is a potential candidate for the treatment of type 2 diabetes and a lead compound for the discovery of novel hypoglycemic drugs. To achieve a thorough understanding of the biological behavior of CAA in vivo, our current study was designed to investigate the pharmacokinetics, bioavailability, distribution, and excretion of CAA in rats by UPLC-MS/MS. Chromatographic separation was performed on BEHC18 column (2.1 mm × 50 mm, 1.7 µm). Quantification was performed under the negative ion mode by using single reaction monitoring (SRM) of the transitions of m/z 353.14 → 309.11 for CAA and m/z 269.86 → 224.11 for genistein, respectively. Standard calibration curve showed excellent linearity (r2 > 0.99) within the range of 2 – 800 ng/mL. The accuracies and precisions were within the acceptance limits (all < 20%). CAA was quickly absorbed into bloodstream and distributed rapidly and widely to various tissues. The excretion ratio of CAA in the 3 main pathways via bile, feces, and urine was only 5.17%. These results indicate that CAA was quickly and thoroughly metabolized in vivo and excreted mainly as metabolites.
Keywords: Pigeon pea; Cajanus cajan; Leguminosae; cajanonic acid A; pharmacokinetics; distribution; excretion; UPLC-MS/MS